Loss of sialic acid side-chain O -acetylation exacerbates colitis - Yang Ji; Shubham Parashar; Yukiko Miyamoto; Saurabh Srivastava; Amanda L. Lewis; Nissi Varki; Ajit Varki; Lars Eckmann (Proceedings of the National Academy of Sciences, 2025)
Sialic acids (Sias) are a diverse family of nine-carbon backbone monosaccharides occupying terminal positions on cell surface and secreted glycans and are abundant at mucosal surfaces. Sias can be modified with O -acetyl esters on the side chain (C7 to C9) hydroxyls. Structural analysis and functional studies of these modifications are challenging due to chemical lability and variable resistance to sialidases. For in-depth analysis of the expression and functions of O -acetyl Sia modifications, we used a unique set of sialoglycan-recognizing probes, HPLC analysis of DMB-derivatized Sias and mice lacking the first known sialate O -acetyltransferase, CASD1. C7/C9- O -acetylated Sias are most abundant in the colon, with lower levels in the heart, brain, and spleen, and minimal levels in other digestive organs of wild-type mice. CASD1 deficiency led to a marked loss of C9/C7- O -acetylated Sias in the colon and other tissues. No differences were observed in colonic O -acetylated Sias from conventional and germ-free wild-type mice, indicating that Sia O -acetylation is independent of the commensal microbiota. Nonetheless, CASD1 deficiency caused subtle changes in microbial gene repertoire consistent with potential exploitation of Sias by subsets of intestinal microbes. Furthermore, CASD1-deficient mice exhibited more severe inflammation and ulceration upon colitis induction compared to controls. Reduced Sia O -acetylation was observed in mice during acute colitis and in colon biopsies from patients with inflammatory bowel disease. Together, our findings suggest CASD1 is the primary physiologically relevant enzyme to add C7/C8/C9- O -acetyl ester groups to Sias and that these Sia modifications exert important gut-protective functions, perhaps by preventing microbial Sia release and metabolism.